Using text messages to promote health in African-Americans: #HeartHealthyandCancerFree*. Issue 3 (3rd April 2018) - Jones, Allison R.; Moser, Debra K.; Hatcher, Jennifer
ABSTRACT: Objectives: African-Americans are vulnerable to both cancer and cardiovascular disease (CVD) due to intricately connected risk factors. Use of text messages is an innovative method to provide health information to reduce these risks. The aim of this study was to test the feasibility and acceptability of a text messaging intervention to reduce CVD and cancer risk factors in African-Americans. Design: We developed an intervention using text messages culturally tailored for African-Americans over age 50 who were at risk (one or more modifiable risk factors) for CVD and/or cancer. Sociodemographic data, biologic measures, cancer screening practices, and general health status were assessed. Group interviews were conducted to assess feasibility and acceptability. Results: Participants were primarily female (69%), aged 58 ± 5 years, who were married (59%) and worked full time (56%). In terms of feasibility and acceptability, themes of encouragement through text messages received and a desire for a longer study period emerged from group interviews with participants. Participants experienced significant decreases in waist circumference (41 ± 5 vs 40 ± 5, p  = .002), systolic blood pressure (147 ± 25 mmHg vs 138 ± 20 mmHg, p  = .009), diastolic blood pressure (87 ± 16 mmHg vs 82 ± 10 mmHg, p  = .02), total cholesterol (194 ± 35 mg/dL vs 173 ± 32 mg/dL, p  < .001), and low-density lipoprotein levels (100 ± 32 mg/dL vs 86 ± 29 mg/dL, p  = .015). Five participants had colorectal cancer screening, two had prostate cancer screening, and four had mammograms. Conclusions: Use of text messages was widely accepted among participants. Significant CVD risk reductions and increased cancer screenings were noted. Future studies should incorporate innovative strategies such as text messaging in promoting health in vulnerable populations.